Bloodless Management of Anaemic HIV Infected Patients in South- South, Nigeria - MBA O., Ozinko; Grace I. , Bassey; Assem M., Ozinko (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2020)
This is a prospective study that aimed at comparing patients’ morbidity and mortality among severely anaemic HIV-patients who were transfused and those who were no transfused. Anaemia is a common presentation among patients with human immunodeficiency virus infection. We treated 13 patients who had packed cell volume ? 20% and were randomized into two groups: group A had blood transfusion while group B did not. Other treatments such as haematinics, antihelminthics, antibiotics, treatment of opportunistic infections, no infusion and balanced nutrition were given to them. The survival rate was higher among those who did not receive blood transfusion while those who were transfused had higher mortality rate. The study concluded that bloodless management of severely anaemic HIV- patients with PCV ? 20% without blood transfusion had higher survival rate than those who were transfused.